(untitled) (Tempo e Argumento, 2016)
Abstract This article analyzes the historical event – a “riot” in Downtown Rio, in June 1987 – by means of photographs published in 5 newspapers from Rio de Janeiro and 1 from Niterói, the day after the event, July 1, 1987. We preliminarily observe the origin of the historiographical concern, where the events were rehabilitated for a historical analysis, above all due to the way how photography was called upon to study them. The reconstruction of the photographic history of the 1987 event is based on the notions of public photography and visual public space, in order to analyze the meanings of the event produced by the newspapers from Rio de Janeiro and evaluate the role played by photojournalism in the making of a historical fact. Keywords: Photography in historiography; Rio de Janeiro (RJ) - History – 1987; Public Spaces - Rio de Janeiro.